Teacher’s Perceptions of Essential Learning Models to Improve Students' Science Learning Achievement in Secondary Schools - Arina Zaida Ilma*; Jumadi Jumadi; Martha Christia Narumsari (Universitas Syiah Kuala, 2022)
Science learning achievement in Indonesia is categorized as still low. A preliminary study based on an interview with science teachers conducted still found students who did not reach the minimum completeness criteria specified in science learning, one of which is influenced by the use of learning models. The research objective is to determine the teacher's perspective on effective learning models to improve students' science learning achievement. The research was conducted in three schools, namely SMP Negeri 1 Nusawungu, SMP Negeri 2 Nusawungu, and SMP Negeri 3 Nusawungu. This research uses descriptive qualitative research with semi-structured interviews. Data collection was carried out by snowball sampling. Respondents in the interview were ten people including five science teachers, two principals, and three curriculum person. The data analysis techniques are data collection, data reduction, data display, and conclusion drawing or verification. The learning models used in schools from the interviews included discovery learning models, cooperative learning, project-based learning, and inquiry learning models. Each learning model can improve students’ science learning achievement. Thus, it can be concluded that an effective learning model to be used in science learning is adjusted to the characteristics of the material or the competencies being taught